A floating Bi@Bi2O3-g-C3N4 hollow glass microsphere catalyst and its preparation method
Patent Information
- Application Number
- CN202410468755.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-18
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-04-18
AI Technical Summary
但该材料主要吸收紫外光,限制了对太阳光的利用效率,且存在回收难题,不利于重复使用,增加了使用成本,同样限制了其大规模应用的潜力
[0017]This invention proposes a floating Bi@Bi2O3-g-C3N4/hollow glass microsphere catalyst and its preparation method. The method is simple to implement, the entire preparation process is safe and environmentally friendly, with no harmful emissions, and the process flow is easy to control. The resulting catalyst has a low density and excellent responsiveness to visible light, achieving efficient degradation of pollutants. It is also easy to recover and reuse, effectively reducing long-term operating costs and providing strong support for industrial-scale applications. In wastewater treatment applications, the floating Bi@Bi2O3-g-C3N4/hollow glass microsphere catalyst of this invention, due to its lower density than water, can stably float on the water surface. This characteristic greatly enhances the catalyst's ability to absorb sunlight, further improving its catalytic efficiency. Simultaneously, the floating characteristic also facilitates rapid catalyst recovery, simplifying the operation process. In summary, the floating Bi@Bi2O3-g-C3N4/hollow glass microsphere catalyst prepared by this invention not only has significant advantages in photocatalytic efficiency but also exhibits low operating costs, achieving both environmental and economic benefits.
Smart Images

Figure CN118437369B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photocatalytic materials technology, specifically, it relates to a floating Bi@Bi2O3-g-C3N4 hollow glass microsphere catalyst and its preparation method. Background Technology
[0002] With rapid economic development, human society has undergone tremendous changes, and material needs have been largely met. However, this has been accompanied by escalating environmental pollution, posing a serious threat to human health. Among numerous environmental problems, water pollution has a particularly significant impact on human health. It not only threatens the safety of daily drinking water but also affects food security through land pollution, causing secondary harm. Therefore, scientists are dedicated to researching effective methods for water pollution control to mitigate its impact on human health. Among various control methods, photocatalysis technology has received widespread attention due to its advantages such as utilizing solar energy and being clean and pollution-free. For example, patent CN116803516A discloses a nitrogen-doped g-C3N4 / BiOBr composite catalyst and its preparation method, which significantly improves the light utilization rate and photocatalytic activity of the material through elemental doping and semiconductor composite strategies. However, the catalyst prepared by this technology suffers from difficulties in recycling and high costs, limiting its large-scale promotion in industrial applications. In addition, patent CN116903880A discloses a method for preparing a sheet-like porous Bi2O3 / ZnO-ZIF-8 heterojunction material. This material has a unique heterojunction, sheet-like, hierarchical porous structure, which enhances its response to ultraviolet light and its adsorption capacity for organic dyes. However, this material mainly absorbs ultraviolet light, limiting its utilization efficiency of sunlight, and it also faces recycling challenges, making it unsuitable for repeated use and increasing its operating costs, thus limiting its potential for large-scale application. Summary of the Invention
[0003] This invention aims to provide a floating Bi@Bi2O3-g-C3N4 hollow glass microsphere catalyst and its preparation method. The preparation process of this invention is simple and highly controllable, and the obtained catalyst exhibits excellent responsiveness to visible light, demonstrating superior degradation efficiency. Furthermore, this catalyst is recyclable and reusable, significantly reducing usage costs and making it a potential candidate for large-scale industrial application. Particularly noteworthy is the use of hollow glass microspheres as a carrier in this invention. This hollow structure not only improves the loading efficiency but also, due to its low density, allows the catalyst to naturally float on the water surface during wastewater treatment, thereby enhancing sunlight absorption and further improving catalytic efficiency.
[0004] The objective of this invention can be achieved through the following technical solutions:
[0005] A method for preparing a floating Bi@Bi2O3-g-C3N4 hollow glass microsphere catalyst includes the following steps:
[0006] a. Mix bismuth oxide, carbon nitride, Triton-X, acetic acid and ethanol, and ball mill at 300-1000 rpm for 0.5-2 hours to obtain a uniformly mixed slurry;
[0007] b. Add hollow glass microspheres to the slurry obtained in step a, stir and mix, let stand, filter, dry and calcine, and after cooling to room temperature, obtain Bi2O3-g-C3N4 / hollow glass microspheres;
[0008] c. The Bi2O3-g-C3N4 / hollow glass microspheres obtained in step b are added to a sodium borohydride solution and stirred for 0.5-1 h. Then, the mixture is filtered, washed, and dried to finally obtain a floating Bi@Bi2O3-g-C3N4 / hollow glass microsphere catalyst.
[0009] Furthermore, the carbon nitride is g-C3N4 (graphitic carbon nitride) to increase the absorption of visible light by the catalyst.
[0010] Furthermore, the hollow glass microspheres undergo an acidification treatment, wherein the acid used in the acidification treatment is selected from at least one of dilute sulfuric acid, dilute nitric acid, and dilute hydrochloric acid, in order to enhance the bonding force between the hollow glass microspheres and the Bi2O3-g-C3N4 coating.
[0011] Furthermore, the preferred mass ratio of bismuth oxide, carbon nitride, Triton-X, acetic acid, and ethanol is (1-2):(2-5):(1-2):1:(5-20).
[0012] Furthermore, the calcination process in step b includes calcination at 250-350℃ for 1-3 hours, followed by calcination at 450-550℃ for 10-60 minutes to form a stable catalyst structure.
[0013] Furthermore, the concentration of the sodium borohydride solution is 0.2-2 mol / L.
[0014] Furthermore, the mass ratio of the Bi2O3-g-C3N4 / hollow glass microspheres to the sodium borohydride solution is 1:(5-15) to ensure the full progress of the reduction reaction.
[0015] Another object of the present invention is to provide a catalyst prepared according to the above preparation method, which can be applied to the field of photocatalytic wastewater treatment and has broad application prospects.
[0016] The beneficial effects of this invention are:
[0017] This invention proposes a floating Bi@Bi2O3-g-C3N4 / hollow glass microsphere catalyst and its preparation method. The method is simple to implement, the entire preparation process is safe and environmentally friendly, with no harmful emissions, and the process flow is easy to control. The resulting catalyst has a low density and excellent responsiveness to visible light, achieving efficient degradation of pollutants. It is also easy to recover and reuse, effectively reducing long-term operating costs and providing strong support for industrial-scale applications. In wastewater treatment applications, the floating Bi@Bi2O3-g-C3N4 / hollow glass microsphere catalyst of this invention, due to its lower density than water, can stably float on the water surface. This characteristic greatly enhances the catalyst's ability to absorb sunlight, further improving its catalytic efficiency. Simultaneously, the floating characteristic also facilitates rapid catalyst recovery, simplifying the operation process. In summary, the floating Bi@Bi2O3-g-C3N4 / hollow glass microsphere catalyst prepared by this invention not only has significant advantages in photocatalytic efficiency but also exhibits low operating costs, achieving both environmental and economic benefits. Attached Figure Description
[0018] To further clarify the details of the present invention, the present invention will be further described below in conjunction with the accompanying drawings.
[0019] Figure 1 This is a SEM image of hollow glass microspheres.
[0020] Figure 2 This is a SEM image of the acidified hollow glass microspheres.
[0021] Figure 3 The image shows a SEM image of the floating Bi@Bi2O3-g-C3N4 / hollow glass microsphere catalyst prepared in Example 1, with a scale bar of 50 μm.
[0022] Figure 4 The image shows a SEM image of the floating Bi@Bi2O3-g-C3N4 / hollow glass microsphere catalyst prepared in Example 1, with a scale bar of 40 μm.
[0023] Figure 5 The image shows a SEM image of the floating Bi@Bi2O3-g-C3N4 / hollow glass microsphere catalyst prepared in Example 1, with a scale bar of 10 μm. Detailed Implementation
[0024] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0025] Photocatalytic performance test of floating Bi@Bi2O3-g-C3N4 / hollow glass microsphere catalyst:
[0026] Using a self-made visible light photocatalytic reaction device, 50 mg of the catalyst prepared in the example was added to 50 mL of a crystal violet (CV) solution with an initial concentration of 10 mg / L. The solution was stirred in the dark for 30 min to allow the system to reach adsorption equilibrium. Then, a 300 W xenon lamp was turned on to carry out the degradation experiment. 2 mL samples were taken at regular intervals, and the concentration of crystal violet in the samples was measured using a UV spectrophotometer.
[0027] Degradation rate (%) = (Initial concentration of crystal violet - Concentration of crystal violet after visible light irradiation) / Initial concentration of crystal violet × 100%.
[0028] Acidification of hollow glass microspheres:
[0029] Take a density of 0.3 g / cm³ 3 100g of hollow glass microspheres with a particle size of 50μm were dispersed in 1000mL of 10% dilute nitric acid and stirred for 4h. The hollow glass microspheres were then filtered and separated, washed with deionized water until neutral, and finally dried in an oven at 100℃ for later use.
[0030] The hollow glass microspheres used in the following examples are all microspheres acidified by this method.
[0031] Example 1
[0032] (1) Take 0.5g bismuth oxide, 1g carbon nitride, 0.6ml Triton-X, 0.45ml acetic acid and 4ml ethanol, mix them and ball mill at 500rpm for 1h to obtain a uniformly mixed slurry;
[0033] (2) Add 2g of the acidified hollow glass microspheres from step (1) to the above slurry, stir for 2h to mix evenly, and let stand for 12h; filter, and then dry in an oven at 100℃ for 4h; finally, put the dried sample into a muffle furnace and keep it at 270℃ for 1h, then raise the temperature to 500℃ and keep it at 0.5h; cool to room temperature to obtain Bi2O3-g-C3N4 / hollow glass microspheres;
[0034] (3) Take 2g of Bi2O3-g-C3N4 / hollow glass microspheres prepared in step (3), add them to 20ml of sodium borohydride solution with a concentration of 0.5mol / L, stir for 0.5h, then filter, wash with deionized water, and finally dry in an oven at 80℃ for 4h to obtain floating Bi@Bi2O3-g-C3N4 / hollow glass microsphere catalyst.
[0035] Among them, SEM images of hollow glass microspheres are displayed, revealing their original surface state and morphological characteristics; SEM images of acidified hollow glass microspheres are shown below. Figure 2 As shown, comparison Figure 2 and Figure 1 It can be clearly observed that the impurities on the surface of the microspheres are effectively removed after acid treatment, resulting in a cleaner surface and providing an ideal substrate for the uniform adhesion of subsequent coatings. Figure 3 SEM images of the prepared floating Bi@Bi2O3-g-C3N4 / hollow glass microsphere catalyst are shown. The images clearly show that a uniform layer of photocatalytic material is coated onto the surface of the hollow glass microspheres, forming a uniform and continuous coating, which provides the catalyst with excellent photocatalytic activity. These SEM images not only provide intuitive information about the hollow glass microspheres and their catalyst coating, but also confirm the effectiveness of the acidification treatment and coating process used in this invention, providing a solid foundation for further optimizing catalyst performance and expanding its application range.
[0036] Example 2
[0037] Except for the fact that the mass of bismuth oxide added in step (1) is 1g, the rest is the same as in Example 1.
[0038] Example 3
[0039] Except for the addition of 2g of carbon nitride in step (1), the rest is the same as in Example 1.
[0040] Example 4
[0041] Except for the addition of 1 ml of Triton-X in step (1), the rest is the same as in Example 1.
[0042] Example 5
[0043] Except for the concentration of the NaBH4 solution added in step (3) being 1 mol / L, the rest is the same as in Example 4.
[0044] Example 6
[0045] (1) Take 1g of bismuth oxide, 3g of carbon nitride, 2ml of Triton-X, 1ml of acetic acid and 10ml of ethanol, mix them and ball mill them at 500rpm for 2h to obtain a uniformly mixed slurry;
[0046] (2) Add 2g of the acidified hollow glass microspheres from step (1) to the above slurry, stir for 2h to mix evenly, and let stand for 14h; filter, and then dry in an oven at 100℃ for 4h; finally, put the dried sample into a muffle furnace and keep it at 270℃ for 1h, then raise the temperature to 500℃ and keep it at 1h; cool to room temperature to obtain Bi2O3-g-C3N4 / hollow glass microspheres;
[0047] (3) Take 2g of Bi2O3-g-C3N4 / hollow glass microspheres prepared in step (3), add them to 15ml of sodium borohydride solution with a concentration of 1mol / L, stir for 1h, then filter, wash with deionized water, and finally dry in an oven at 80℃ for 4h to obtain floating Bi@Bi2O3-g-C3N4 / hollow glass microsphere catalyst.
[0048] Example 7
[0049] (1) Take 1g of bismuth oxide, 5g of carbon nitride, 2ml of Triton-X, 1ml of acetic acid and 20ml of ethanol, mix them and ball mill them at 500rpm for 2h to obtain a uniformly mixed slurry;
[0050] (2) Add 2g of the acidified hollow glass microspheres from step (1) to the above slurry, stir for 2h to mix evenly, and let stand for 14h; filter, and then dry in an oven at 100℃ for 4h; finally, put the dried sample into a muffle furnace and keep it at 270℃ for 1h, then raise the temperature to 500℃ and keep it at 0.5h; cool to room temperature to obtain Bi2O3-g-C3N4 / hollow glass microspheres;
[0051] (3) Take 2g of Bi2O3-g-C3N4 / hollow glass microspheres prepared in step (3), add them to 15ml of sodium borohydride solution with a concentration of 2mol / L, stir for 1h, then filter, wash with deionized water, and finally dry in an oven at 80℃ for 4h to obtain floating Bi@Bi2O3-g-C3N4 / hollow glass microsphere catalyst.
[0052] Example 8
[0053] (1) Take 2g of bismuth oxide, 5g of carbon nitride, 2ml of Triton-X, 1ml of acetic acid and 10ml of ethanol, mix them and ball mill them at 1000rpm for 1h to obtain a uniformly mixed slurry;
[0054] (2) Add 2g of the acidified hollow glass microspheres from step (1) to the above slurry, stir for 2h to mix evenly, and let stand for 10h; filter, and then dry in an oven at 100℃ for 4h; finally, put the dried sample into a muffle furnace and keep it at 270℃ for 2h, then raise the temperature to 500℃ and keep it at 0.5h; cool to room temperature to obtain Bi2O3-g-C3N4 / hollow glass microspheres;
[0055] (3) Take 2g of Bi2O3-g-C3N4 / hollow glass microspheres prepared in step (3), add them to 20ml of sodium borohydride solution with a concentration of 1mol / L, stir for 1h, then filter, wash with deionized water, and finally dry in an oven at 80℃ for 4h to obtain floating Bi@Bi2O3-g-C3N4 / hollow glass microsphere catalyst.
[0056] The photocatalytic performance test results of the floating Bi@Bi2O3-g-C3N4 / hollow glass microsphere catalysts in Examples 1-8 are shown in Table 1.
[0057] Table 1
[0058] Example 1 75.5 Example 2 74.8 Example 3 74.2 Example 4 76.1 Example 5 77.2 Example 6 76.8 Example 7 77.5 Example 8 75.3
[0059] Through the Figure 1 and Figure 2 Through observation, we can clearly see that impurities on the surface of the hollow glass microspheres are effectively removed after acidification. This step not only preserves the surface characteristics of the glass microspheres but also provides a more uniform and stable adhesion base for the subsequent Bi2O3-g-C3N4 coating. Furthermore, the acidification treatment significantly enhances the bonding force between the hollow glass microspheres and the Bi2O3-g-C3N4 coating, which is crucial for improving the overall performance of the catalyst. Further, according to... Figures 3 to 5 As shown, Bi@Bi2O3-g-C3N4 in this invention is uniformly distributed on the surface of hollow glass microspheres. This distribution is beneficial to fully utilize the photocatalytic performance of the catalyst and ensures the high efficiency of the photocatalytic reaction.
[0060] Based on the visible light degradation rate results of crystal violet in Examples 1-8 in Table 1, the floating Bi@Bi2O3-g-C3N4 / hollow glass microsphere catalyst obtained by the preparation method of this application exhibits good absorption characteristics for visible light, and its photocatalytic effect is significant, showing excellent degradation rate of pollutants.
[0061] In summary, the preparation method provided by this invention can successfully prepare a floating Bi@Bi2O3-g-C3N4 / hollow glass microsphere catalyst with excellent photocatalytic effect. This catalyst exhibits excellent performance under visible light irradiation, the preparation process is environmentally friendly and non-toxic, the process is controllable, and the catalyst is easy to recover and reuse, greatly reducing costs and laying a solid foundation for its large-scale application in the industrial field.
[0062] The above detailed embodiments provide a specific description of the analytical methods involved in this invention. It should be noted that the above description is only intended to help those skilled in the art better understand the methods and ideas of this invention, and is not intended to limit the scope of the invention. Without departing from the principles of this invention, those skilled in the art can make appropriate adjustments or modifications to this invention, and such adjustments and modifications should also fall within the protection scope of this invention.
Claims
1. A method for preparing a floating Bi@Bi2O3-g-C3N4 hollow glass microsphere catalyst, characterized in that, Includes the following steps: a. Mix bismuth oxide, carbon nitride, Triton-X, acetic acid and ethanol, and ball mill at 300-1000 rpm for 0.5-2 hours to obtain a uniformly mixed slurry; b. Add hollow glass microspheres to the slurry obtained in step a, stir and mix, let stand, filter, dry and calcine, and after cooling to room temperature, obtain Bi2O3-g-C3N4 / hollow glass microspheres; The hollow glass microspheres are subjected to an acidification treatment, wherein the acid used in the acidification treatment is selected from at least one of dilute sulfuric acid, dilute nitric acid and dilute hydrochloric acid; c. The Bi2O3-g-C3N4 / hollow glass microspheres obtained in step b are added to a sodium borohydride solution and stirred for 0.5-1 h. Then, the mixture is filtered, washed, and dried to finally obtain a floating Bi@Bi2O3-g-C3N4 / hollow glass microsphere catalyst.
2. The method for preparing a floating Bi@Bi2O3-g-C3N4 hollow glass microsphere catalyst according to claim 1, characterized in that, The carbon nitride is g-C3N4.
3. The method for preparing a floating Bi@Bi2O3-g-C3N4 hollow glass microsphere catalyst according to claim 1, characterized in that, The mass ratio of bismuth oxide, carbon nitride, Triton-X, acetic acid and ethanol is (1-2):(2-5):(1-2):1:(5-20).
4. The method for preparing a floating Bi@Bi2O3-g-C3N4 hollow glass microsphere catalyst according to claim 1, characterized in that, The calcination process in step b includes calcination at 250-350℃ for 1-3 hours, followed by calcination at 450-550℃ for 10-60 minutes.
5. The method for preparing a floating Bi@Bi2O3-g-C3N4 hollow glass microsphere catalyst according to claim 1, characterized in that, The concentration range of the sodium borohydride solution is 0.2-2 mol / L.
6. The method for preparing a floating Bi@Bi2O3-g-C3N4 hollow glass microsphere catalyst according to claim 1, characterized in that, The sodium borohydride solution is used to reduce Bi2O3 to elemental Bi, wherein the mass ratio of Bi2O3-g-C3N4 / hollow glass microspheres to sodium borohydride solution is 1:(5-15).
7. A floating Bi@Bi2O3-g-C3N4 hollow glass microsphere catalyst, characterized in that, Prepared by the method according to any one of claims 1-6.
Citation Information
Patent Citations
Preparation method and application of flaky porous Bi2O3 / ZnO-ZIF-8 heterojunction material
CN116903880A
Amorphous bismuth oxide hybrid photocatalyst, preparation method and usage method
CN107051422A